Biomonitoring of Heavy Metal Plumbum (Pb) in Spermonde Island Makassar Using Starfish as Bio-Indicator (Protoreaster nodosus) - Lili Amalia; Musa Ramang (Hasanuddin University, 2014)
Biomonitoring is a method of monitoring water quality using biological indicators (bioindicator). This study aims to develop methods of biomonitoring and potential of the marine biota as bioindi- cator for marine pollution. To optimize the analysis, samples suspected to contain heavy metals Pb were taken at three points from three different locations, and a point at random from a single loca- tion in Makassar Spermonde Islands, using AAS asanalytical techniques.The results showed that Pb levels in starfish Protoreaster nodosus types ranged from 2,6080 to 2,8876 ppm, bigger than the distribution in the sediment ranged between 0,4862 to 0,5582 ppm and in sea water ranges between 0,6732 to 0,8724 ppm. The results obtained have exceeded the threshold of water quality standards.